2019
DOI: 10.3390/ijms20184387
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Anthocyanins in Green and Purple Turnips Revealed by Combined De Novo Transcriptome and Metabolome Analysis

Abstract: Purple turnip Brassica rapa ssp. rapa is highly appreciated by consumers but the metabolites and molecular mechanisms underlying the root skin pigmentation remain open to study. Herein, we analyzed the anthocyanin composition in purple turnip (PT) and green turnip (GT) at five developmental stages. A total of 21 anthocyanins were detected and classified into the six major anthocynanin aglycones. Distinctly, PT contains 20 times higher levels of anthocyanins than GT, which explain the difference in the root ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 80 publications
3
62
0
1
Order By: Relevance
“…Variation of anthocyanin content in plant tissues is ascribed to the differential expression levels of key genes participating in the biosynthetic pathway [51]. Comparison of cultivars with contrasting fruit flesh colors allowed us to identify differentially expressed anthocyanin biosynthetic genes that may affect the color formation as previously documented in turnip [52], Prunus mira [53] and Lagerstromemia indica [54]. Interestingly, 12 key genes were highlighted in this study, seven of which directly involved in the anthocyanin biosynthetic pathway, were found significantly higher expressed in the colored cultivars (red and pink) as compared to the white cultivar.…”
Section: Discussionmentioning
confidence: 98%
“…Variation of anthocyanin content in plant tissues is ascribed to the differential expression levels of key genes participating in the biosynthetic pathway [51]. Comparison of cultivars with contrasting fruit flesh colors allowed us to identify differentially expressed anthocyanin biosynthetic genes that may affect the color formation as previously documented in turnip [52], Prunus mira [53] and Lagerstromemia indica [54]. Interestingly, 12 key genes were highlighted in this study, seven of which directly involved in the anthocyanin biosynthetic pathway, were found significantly higher expressed in the colored cultivars (red and pink) as compared to the white cultivar.…”
Section: Discussionmentioning
confidence: 98%
“…A number of studies about transcriptomics and metabonomics in anthocyanin biosynthesis revealed that the expression levels of structural genes play an important role in anthocyanin accumulation, especially DFR, ANS, and F3H [55][56][57][58]. DFR and ANS are considered as very important enzymes in anthocyanin biosynthesis, as they could direct the flavonoid flux into the anthocyanin branch [55][56][57][58]. Previous studies showed that the expression levels of DFR, ANS, and F3H and some transcription factors were positively correlated with anthocyanin accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Anthocyanin, a class of flavonoids, localized in vacuoles, provided a wide range of colors ranging from orange/red to violet/blue. The content and variety of anthocyanins are the primary determinants of color in many fruit peel and flesh or flowers; the family of MYB and WD40 transcription factors and DFR and CHS had significant regulatory function on anthocyanin synthesis ( Wang et al, 2019 ; Zhuang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%